Cyclodextrins as Drug Carriers in Pharmaceutical Technology: The State of the Art - Conceicao, Jaime; Adeoye, Oluwatomide; Cabral-Marques, Helena M.; Lobo, Jose M. S. (Current Pharmaceutical Design, 2018)
Background: Cyclodextrins (CDs) are versatile excipients with an essential role in drug delivery, as they can form non-covalently bonded inclusion complexes (host-guest complexes) with several drugs either in solution or in the solid state. Methods: The main purpose of this publication was to carry out a state of the art of CDs as complexing agents in drug carrier systems. In this way, the history, properties and pharmaceutical applications of the CDs were highlighted with typical examples. The methods to enhance the Complexation Efficiency (CE) and the CDs applications in solid dosage forms were emphasized in more detail. Results: The main advantages of using these cyclic oligosaccharides are as follows: (1) to enhance solubility/ dissolution/ bioavailability of poorly soluble drugs; (2) to enhance drug stability; (3) to modify the drug release site and/or time profile; and (4) to reduce drug side effects (for example, gastric or ocular irritation). These compounds present favorable toxicological profile for human use and therefore there are various medicines containing CDs approved by regulatory authorities worldwide. On the other hand, the major drawback of CDs is the increase in formulation bulk, once the CE is, in general, very low. This aspect is particularly relevant in solid dosage forms and limits the use of CDs to potent drugs. Conclusion: CDs have great potential as drug carriers in Pharmaceutical Technology and can be used by the formulator in order to improve the drug properties such as solubility, bioavailability and stability. Additionally, recent studies have shown that these compounds can be applied as active pharmaceutical ingredients.
Keywords: drug carriers